Currículo como construção social em contexto de cidadania intercultural indígena - Julião, Geisel Bento (2011)
This study analyses the reconstruction of indian schools in Roraima. I have started with the hypothesis that the exercise of citizenship of the intercultural indigenous population has assumed a prominent part in the construction, and an understanding of this is necessary. For this, in the first chapter I have discussed the historical process of the colonisation of the indigenous people of Roraima. To follow up, I have written about the fights and successes, especially in the educational area, since the middle of 1968 to the present day. In the second chapter I have made a discussion about the concept of intercultural indigenous citizenship with a view to giving a fundamental theory to the study. In the third chapter, I have focused on an analysis about the day-to-day life of the community researched (Anta II) and the three environments of the formation of the indigenous citizen, which are: the family, the community and the indigenous meeetings and assemblies. In the fourth and final chapter, I have discussed the school and as to whether the formulation of the curriculum has the social capacity to make a school an institution able to promote intercultural indigenous citizens. The Indigenous State School, Geraldo Julião, located in the indigenous community Anta II, Anta Indigenous land, in the municipality of Alto Alegre, State of Roraima was the school reference for the field research. The methodology was qualitative with a focus on bibliographical and field research; this final support being by interview and personal participation in meetings and assemblies